Glutamic acid codon suppressors derived from a unique species of glycine transfer ribonucleic acid. - Murgola, E J (1980)
In this paper we describe the successful isolation of glyT-derived GAA suppressors. A glyT+ strain containing glyV55, the gene for a GGA/G-reading, methane sulfonate and hydroxylamine. The cells were plated to select for reversal of auxotrophy due to a trpA(GAA211) mutation. With either mutagen, greater than 85% of the prototrophs obtained were due to suppressors of the trpA mutation. Approximately 12% of the ethyl methane sulfonate-induced and 37% of the hydroxylamine-induced suppressors were shown to be about 25% cotranscucible with metB, as is glyT. The transfer ribonucleic acid from four metB-linked suppressor strains (two from each mutagen) was examined by reversed-phase column (RPC-5) chromatography. In all four cases, the glycyl-transfer ribonucleic acid profile displayed an alteration of glyT transfer ribonucleic acid. All four suppressors responded to GAG in addition to GAA but did not suppress the known mutant codons of several other trpA mutants. Other properties are discussed, along with possible reasons for our success in obtaining these suppressors.